Research on Teaching Reform and Talent Development Pathways for Garment Construction Courses in Vocational Colleges Driven by 3D Virtual Simulation from a Constructivist Perspective - Cao, Yupei (Journal of Research in Vocational Education, 2026)
With the rapid advancement of digital technologies in the global fashion industry, vocational education is undergoing a profound transformation from traditional skill-oriented models toward innovation- and digital-competency-integrated paradigms. Addressing the prevalent challenges faced by Garment Construction courses in vocational colleges during their digital transformation, including the absence of authentic industry contexts, the disconnect between structural logic and creative thinking, and insufficient integration between digital tools and knowledge systems, this study adopts constructivist learning theory as its theoretical foundation and employs 3D virtual simulation technology to develop an integrated spiral teaching model that encompasses “foundational knowledge—operational skills—creative expression—reflective transfer.” The research integrates digital interactive technologies including Virtual Reality (VR), Augmented Reality (AR), and 3D digital twins to design multi-tiered contextual learning tasks, systematically reconstructing the course’s objective framework, content architecture, instructional processes, and assessment mechanisms. Additionally, it conducts an in-depth analysis of the correspondence between course modules and competency requirements for positions related to garment construction. The findings demonstrate that the constructivist teaching model driven by 3D virtual simulation significantly enhances students’ cognitive depth in understanding garment structural logic and technological processes, while effectively promoting the transfer and development of digital thinking and innovative capabilities. This approach establishes a new talent cultivation mechanism in vocational education characterized by “virtual-real integration, task-driven learning, and reflective generation.” This study provides practical reform pathways and theoretical paradigms for curriculum system reconstruction and pedagogical innovation in fashion design programs at vocational colleges in the digital-intelligent era.